2010
DOI: 10.5539/ijbm.v5n11p3
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Stress in Organization, a Case Study of Sukkur

Abstract: The aim of this study is to investigate the main causes of stress for employees working in different industries in Sukkur and their vicinity. Stress is taken as dependent variable whereas independent variables are categorized into extra-organizational and intra-organizational stressors. Data were collected from different sectors such service, manufacturing and distribution including banks, insurance companies, manufacturing (LU Continental Biscuit Factory Sukkur and Engro Foods) and distribution (Medicine dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
0
12
0
4
Order By: Relevance
“…Organizational support theory (OST) argues that employees tend to form a general perception of the extent to which the organization values their contributions and is concerned about their well-being, in order to meet the socio-emotional needs and assess the benefits of a greater work effort [32,41,42]. According to the literature [43], social support and, in particular, the POS can lead to increased levels of adjustment and the professional success of expatriates. Individuals with a high level of POS may meet the expectations of their supervisors and co-workers by showing proactive approaches to problem resolution and positive attitudes toward hard work [44].…”
Section: Perceived Organizational Support (Pos) and Ccamentioning
confidence: 99%
“…Organizational support theory (OST) argues that employees tend to form a general perception of the extent to which the organization values their contributions and is concerned about their well-being, in order to meet the socio-emotional needs and assess the benefits of a greater work effort [32,41,42]. According to the literature [43], social support and, in particular, the POS can lead to increased levels of adjustment and the professional success of expatriates. Individuals with a high level of POS may meet the expectations of their supervisors and co-workers by showing proactive approaches to problem resolution and positive attitudes toward hard work [44].…”
Section: Perceived Organizational Support (Pos) and Ccamentioning
confidence: 99%
“…Supported by [26] that the size of the firm is considered to affect the value of the firm because the larger the size of the firm then the easier it is for the firm to obtain a source of funding that can be used to achieve the firm's goals. [27] Defines Islamic Corporate Governance as governance based on Islamic principles, where business and operational activities are carried out based on moral and sharia values. [27] in his research also revealed two unique features of Islamic Corporate Governance, namely the first, that the regulated by Islamic or sharia law and governs all aspects of an individual's life, in Islam every Muslim's actions must be in accordance with sharia and they must ethical standards set by Islam.…”
Section: Firm Valuementioning
confidence: 99%
“…[27] Defines Islamic Corporate Governance as governance based on Islamic principles, where business and operational activities are carried out based on moral and sharia values. [27] in his research also revealed two unique features of Islamic Corporate Governance, namely the first, that the regulated by Islamic or sharia law and governs all aspects of an individual's life, in Islam every Muslim's actions must be in accordance with sharia and they must ethical standards set by Islam. [28] revealed that ICG is trying to combine Islamic law with stakeholder models in corporate governance.…”
Section: Firm Valuementioning
confidence: 99%
“…The first factor in the model RO has significant positive influence on JS [31] resulting poor JSF [17]. Empirical evidence have revealed that RO is associated to a variety of physiological and behavioral attitudes appearing in the form of JS, burnout, and job dissatisfaction [32].…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%